2022
DOI: 10.1002/cssc.202201284
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Modification Technologies of Lignin‐based Activated Carbon toward Advanced Applications

Abstract: Lignin-based activated carbon (LAC) is a promising high-quality functional material due to high surface area, abundant porous structure, and various functional groups. Modification is the most important step to functionalize LAC by altering its porous and chemical properties. This Review summarizes the state-ofthe-art modification technologies of LAC toward advanced applications. Promising modification approaches are reviewed to display their effects on the preparation of LAC. The multiscale changes in the por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…These products typically exhibit a high concentration of oxygen functional groups and a low degree of aromatization, rendering them effective precursors for chemical activation [91]. The hydrothermal carbonization of lignin for the production of activated carbon derived from lignin generates reduced CO 2 emissions compared to traditional carbonization methods and eliminates the need for protective gas flow [92]. The procedure involves subjecting lignin to hydrothermal treatment for carbonization, followed by mixing the resulting dried product with KOH to create lignin-based activated carbon.…”
Section: Activated Carbonmentioning
confidence: 99%
“…These products typically exhibit a high concentration of oxygen functional groups and a low degree of aromatization, rendering them effective precursors for chemical activation [91]. The hydrothermal carbonization of lignin for the production of activated carbon derived from lignin generates reduced CO 2 emissions compared to traditional carbonization methods and eliminates the need for protective gas flow [92]. The procedure involves subjecting lignin to hydrothermal treatment for carbonization, followed by mixing the resulting dried product with KOH to create lignin-based activated carbon.…”
Section: Activated Carbonmentioning
confidence: 99%
“…There has been a lot of research on developing advanced carbon structures based on lignin. 2,[82][83][84][85][86][87] In respect to ordered mesoporous carbons, so far, it was shown that in the typical so-templating method, about half of phloroglucinol can be replaced by lignin, 68 and even more when metal ions are added due to the coordination-assisted self-assembly. 74,88 It would be interesting to explore whether other types of lignin can be a better t to the so-templating method, to shed light on structural requirements/benets for facilitating the selfassembly.…”
Section: Critical Outlookmentioning
confidence: 99%
“…[ 10,11 ] Unfortunately, the existence of hemicellulose tremendously hinders the lateral growth of carbon crystals, and the presence of lignin extensively forms stable amorphous carbon. [ 12,13 ] Therefore, it is still crucial for conductive biomass carbon to rationally develop the highly graphitized microcrystals (hGMCs).…”
Section: Introductionmentioning
confidence: 99%